Correction: Development of the Italian version of the Orgasmic Perception Questionnaire (OPQ). - Marta Panzeri; Denise Mauro; Lucia Ronconi; Ana Isabel Arcos-Romero (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0288850.].